A Novel Lidar Ceilometer - Vande Hey, Joshua D (Springer, 2015)
In this thesis, a new lidar (light detection and ranging) ceilometer capable of monitoring cloud base and sensitive to boundary layer aerosols is introduced. The key to this novelty lies in its divided-lens design that addresses a classical lidar problem of balancing transmitter-receiver overlap and signal-to-noise ratio, along with a method for characterizing overlap in the laboratory. Enhanced sensitivity in the near-range of the instrument is achieved without compromising signal-to-noise in a design that is straightforward to manufacture for broad deployment. The instrument, its optical characterization, and its performance in the field are described. The prototype instrument described here has since formed the basis of a commercial sensor for monitoring clouds and aerosols.